2005
DOI: 10.1007/s11934-005-0040-3
|View full text |Cite
|
Sign up to set email alerts
|

Lower urinary tract symptoms and erectile dysfunction: Epidemiology and treatment in the aging man

Abstract: Lower urinary tract symptoms (LUTS) and erectile dysfunction (ED) are common urologic problems that are seen in the aging male population. Until recently, aging itself was considered the common link between ED and LUTS. However, recent studies have shown that the links between these two disease processes are much more complex and are possibly inter-related with a common mechanism. This newly recognized independent relationship between ED and LUTS has the potential to have a profound impact on the way we diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 57 publications
0
9
0
1
Order By: Relevance
“…Similarly, in 2003, Braun et al reported a strong association between LUTS and ED in a German cohort of 4489 men [34]. The coexistence of ED and LUTS may indicate that BMI is implemented in LUTS pathogenesis [17,19,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in 2003, Braun et al reported a strong association between LUTS and ED in a German cohort of 4489 men [34]. The coexistence of ED and LUTS may indicate that BMI is implemented in LUTS pathogenesis [17,19,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…3 This is presumably due to an inadequate activation of neuronal nitric oxide synthase (nNOS) and subsequent defective production of nitric oxide (NO). 4 Decreased NO bioavailability impairs vasodilation and enhances formation of reactive oxygen species (ROS) that can cause tissue damage.…”
Section: Pathogenesis Of Edmentioning
confidence: 99%
“…Since aging is one of the main risk factors for erectile dysfunction, most men during their lifetime will at some time be afflicted with this condition [1][2][3]. It is becoming increasingly apparent that the main culprit for erectile dysfunction in the majority of patients is corporal venoocclusive dysfunction (CVOD) [4,5].…”
Section: Introductionmentioning
confidence: 99%